Direct Radiative Effect by Mineral Dust Aerosols Constrained by New Microphysical and Spectral Optical Data. Issue 2 (23rd January 2020) - Di Biagio, C.; Balkanski, Y.; Albani, S.; Boucher, O.; Formenti, P.
Abstract: We revise the direct radiative effect (DRE) of mineral dust aerosols in the shortwave (SW) and longwave (LW) based on global model simulations that include coarse dust particles (>20 μm) and a new LW complex refractive index data set representative of major global sources. Simulations are constrained against observed dust size distributions and optical depth. Scattering of LW radiation is accounted for in the analysis. The extension of the dust size beyond 20 μm causes a reduction in the SW DRE compared to current model estimates, while the LW DRE remains within published values due to compensating effects between changing size distribution, complex refractive index, and accounting for dust scattering. The dust direct radiative effect efficiency from model simulations reproduces well field observations close to sources and after transport. The global mean net effect of dust is −0.03 Wm −2 as a result of cooling over oceans and warming over land. Key Points: New global dust simulations including particles >20 μm, refractive index representative of world sources, and longwave scattering correction The global dust longwave effect remains within published values while the shortwave one is reduced due to the inclusion of coarse particles Varying the longwave refractive index within its documented range of variability modifies the sign of the net global dust direct effect